2021
DOI: 10.3390/diagnostics12010086
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Long Non-Coding RNA GAS5 and MicroRNA-222 in Younger AML Patients

Abstract: Acute myeloid leukemia (AML) is a heterogeneous malignant disease both on clinical and genetic levels. AML has poor prognosis and, therefore, there is a constant need to find new prognostic markers, as well as markers that can be used as targets for innovative therapeutics. Recently, the search for new biomarkers has turned researchers’ attention towards non-coding RNAs, especially long non-coding RNAs (lncRNAs) and micro RNAs (miRNAs). We investigated the expression level of growth arrest-specific transcript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…AML is a heterogeneous malignant hematologic tumor. Chromosomal translocation is the commonest cause of the malignant transformation of hematopoietic progenitor cells [20]. AML patients suffer mainly * indicated that the comparison with NC group showed remarkable difference (P < 0:05).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AML is a heterogeneous malignant hematologic tumor. Chromosomal translocation is the commonest cause of the malignant transformation of hematopoietic progenitor cells [20]. AML patients suffer mainly * indicated that the comparison with NC group showed remarkable difference (P < 0:05).…”
Section: Discussionmentioning
confidence: 97%
“…AML is a heterogeneous malignant hematologic tumor. Chromosomal translocation is the commonest cause of the malignant transformation of hematopoietic progenitor cells [ 20 ]. AML patients suffer mainly from the blocking of normal differentiation and apoptosis of hematopoietic cells, the abnormal proliferation of bone marrow hematopoietic cells, and the accumulation of a large number of immature progenitor cells in the bone marrow peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in AML GAS5 has a tumor-suppressive function and it was also found that lower expression of GAS5 was associated with inferior outcome among younger AML-NK patients [85]. As is the case with CLL, in AML GAS5 exerts its tumor-suppressor function, acting as a decoy for miR-222 [85].…”
Section: Lncrna Gas5mentioning
confidence: 91%
“…There are only few studies examining GAS5 in AML, one of them examining GAS5 gene polymorphisms and their impact on AML prognosis [84]., Only two studies were investigating expression level of GAS5 in AML samples and based on their findings GAS5 expression level in AML patients was lower compared to healthy controls [82,85]. This suggests that in AML GAS5 has a tumor-suppressive function and it was also found that lower expression of GAS5 was associated with inferior outcome among younger AML-NK patients [85]. As is the case with CLL, in AML GAS5 exerts its tumor-suppressor function, acting as a decoy for miR-222 [85].…”
Section: Lncrna Gas5mentioning
confidence: 99%
“…Additionally, the lncRNA growth arrest-specific transcript 5 (GAS5) acts as both a negative regulator of the oncogenic miR-222 and a positive regulator of the tumor suppressor PTEN. Pavlovic et al observed lower levels of GAS5 in sAML compared with healthy donors [ 127 ].…”
Section: Cytogenetics and Mutational Landscape Of Samlmentioning
confidence: 99%